Fake news and asset price dynamics - Sarah Mignot; Paolo Pellizzari; Frank H. Westerhoff (Bamberg University, Bamberg Economic Research Group (BERG), 2024)
We explore the impact of fake news on asset price dynamics within the asset-pricing model of Brock and Hommes (1998). By polluting the information landscape, fake news interferes with agents' perception of the dividend process of the risky asset. Our analysis reveals that fake news decreases the steady-state price of the risky asset by making it even more risky. Moreover, fake news increases the market share of agents who use the destabilizing technical trading rule by rendering fundamental trading more difficult and costly. Instead of converging toward its steady state, the risky asset's price may thus be subject to wild fluctuations. As it turns out, these fluctuations are concentrated below the risky asset's steady-state price. We also show that fake news campaigns may allow certain agents to realize fraudulent profits.
Keywords: G12; G14; G41; 330; Asset price dynamics; fake news; chartists and fundamentalists; bounded rationality and learning; stability and bifurcation analysis